2013
DOI: 10.1212/wnl.0b013e31827f0846
|View full text |Cite
|
Sign up to set email alerts
|

Patients with unresponsive wakefulness syndrome respond to the pain cries of other people

Abstract: Although there is debate about whether patients with UWS can perceive their own pain, our data indicate that many of them respond to the signals of pain in others. One can speculate that "affective consciousness" can remain even in patients with very severe brain damage who have no capacity for cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 40 publications
(35 reference statements)
4
32
0
2
Order By: Relevance
“…Furthermore, two other studies reported an activation of the affective pain network (i.e. ACC and insula) in 30% of patients in a VS/UWS in response to noxious stimulation as well as pain cries [27,28] (Figure 1). The last study, nevertheless, also showed, in parallel to previous findings, that the connectivity within the whole pain network was significantly decreased as compared to patients in a MCS [29].…”
Section: Pain Processing and Disorders Of Consciousnessmentioning
confidence: 90%
“…Furthermore, two other studies reported an activation of the affective pain network (i.e. ACC and insula) in 30% of patients in a VS/UWS in response to noxious stimulation as well as pain cries [27,28] (Figure 1). The last study, nevertheless, also showed, in parallel to previous findings, that the connectivity within the whole pain network was significantly decreased as compared to patients in a MCS [29].…”
Section: Pain Processing and Disorders Of Consciousnessmentioning
confidence: 90%
“…However, cognitive function detected by current technologies is still unable to reliably prove the consciousness of a DOC patient. Brain activity alone cannot prove patient consciousness, though it has been hypothesized that consciousness is associated with brain activity (27). Importantly, a fundamental distinction between consciousness and unconsciousness is yet to be determined.…”
Section: Reliability Of Novel Diagnostic Technologiesmentioning
confidence: 99%
“…As a result, we must be careful not to rule out the possibility that a patient is sentient simply because she has not demonstrated awareness. For example, a study by Yu and colleagues found that 24 of 44 patients diagnosed as vegetative demonstrated significant neural activation in response to the pain cries of others, with four demonstrating activation virtually identical to those of healthy subjects (Yu et al 2013). These findings are consistent with the view that affective states (e.g., pain and pleasure) may be more basic elements of consciousness, as opposed to the more complex elements implied by cognitive awareness (e.g., attention, working memory, and language comprehension) (Panksepp 2005).…”
Section: Pain: a Multidimensional Experiencementioning
confidence: 99%